Optimalisasi Fasilitas Pendidikan di Provinsi Lampung (Studi Kasus Komparasi Sekolah SMA Swasta dan Negeri) - Bustomi, Ahmad; Zuhairi, Zuhairi; Nurida, Safira; Sintiya, Farra; Isroani, Farida (Tarbawiyah Jurnal Ilmiah Pendidikan, 2023)
SMK Muhammadiyah 1 Metro and MAN 1 East Lampung have the same problem, namely the lack of adequate facilities hinders learning activities so that the learning process becomes less conducive. This study aims to find out how the facilities and infrastructure in private and public schools are. This research is a type of field research with a qualitative approach. Data collection methods used are interviews, observation and documentation. The results of this study are that the two schools studied have similarities and differences that occur. In general, the physical form of school buildings has many similarities, for example classrooms, mosque buildings, toilets, sports fields, art rooms, laboratory rooms, computer rooms, library rooms, UKS rooms, OSIS/extracurricular activity rooms, school canteens, and etc. On the other hand, the differences found in the two schools can be seen in terms of maintenance and cleanliness. Keywords: Educational facilities, Comparison of Schools, State Aliyah Madrasah, Vocational High School.